Ethical Leadership of School Heads and Emotional Intelligence of Teachers: Basis for Action Plan - Salvador, Dolid (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the level of ethical leadership practices of school heads and the emotional intelligence of teachers in the Schools Division of Ifugao. Using a descriptive-correlational research design, data were collected from 121 respondents, comprising 110 teachers and 11 school heads. The results showed that school heads had a high level of ethical leadership (M = 3.57), specifically in respectful communication, modeling of ethical behavior and promoting ethical values. Teachers also exhibited a very high level of emotional intelligence (M = 3.29), with strengths in social awareness and inclusive practice, self-awareness and professionalism, interpersonal relationship and relationship building. On the other hand, the score in emotional regulation and self-control is somewhat lower (M=3.05) but still interpreted as high. Data analysis showed no significant differences in ethical leadership practices when grouped according to age, sex, years in service, and educational attainment, indicating consistency across demographic profiles. However, a significant positive relationship was found between ethical leadership and teachers’ emotional intelligence (r = .470, p < .01), suggesting that ethical leadership is a strong predictor of teachers’ emotional intelligence resulting to a very high social awareness of teachers. The study concludes that ethical leadership plays an essential role in fostering teachers’ emotional intelligence, contributing to a positive school climate and effective professional relationships. Nonetheless, areas such as emotional regulation, communication openness, and decision-making consistency require further enhancement. The findings highlight the need for continuous leadership training and professional development programs focusing on both ethical leadership and emotional intelligence.
Keywords: Ethical Leadership; Emotional Intelligence; Relationship-Building; Social Awareness; Professional Development; School Climate